The Benefits of a Culture of Providing Rewards and Appreciations to Organization Members to Improve Performance - Hadijaya, Yusuf; Mujahid, Tamimi; Astika, Lilis; Ramadina, Rifda (Pusdikra-Publishing.com, 2024)
Culture is a set of values, beliefs, and attitudes that guide an organization's strategic goals and objectives directions. Rewards are bonuses or appreciation given to organizational members for their consistency and good performance. Of course, this encourages the involvement of organizational members and teaches organizational values ??which can result in higher growth. The research method used in this research is the library research method by concluding previous research or literature review. The purpose of this research is to determine the benefits of providing rewards for the performance of organizational members. Organizational culture is the basis or basis for the similarity of opinions and beliefs as well as practical values ??for all members of the organization. Rewards can also be said to be a culture in an organization, where they can attract employees' attention and provide information or remind them of the importance of the thing being rewarded compared to others.